OPPORTUNITIES FOR THE APPLICATION OF THE GUT-BRAIN-AXIS MICROBIOTA FOR THE OPTIMIZATION OF NERVE GROWTH AND DEVELOPMENT IN INFANTS - Allatib, Arohid; Azzahra, Zahwa Arsy; Widyaningrum, Immaculata; Januarta, Cahya Wahyudi (Jurnal Ilmu Kedokteran dan Kesehatan, 2023)
Abstract: Opportunities for The Application of The Gut-Brain-Axis Microbiota for The Optimization of Nerve Growth and Development in Infants. Neurodevelopment in infants is very important and has a significant role in shaping their future intellectual, emotional, and physical capacities. Nerve cells (neurons) form a neural network in babies from the time of pregnancy. The interaction between the gut microbiota and the brain occurs through a pathway called the gut-brain axis. Studies have shown that gut microbiota influences brain function and human behavior. To find out the efforts that can be made to maximize the development of the baby's brain by utilizing the concept of the gut-brain-axis microbiota. Using literature review techniques from international articles in the 2013-2023 using specific keywords in PubMed, Cochrane, Embase, Scopus, Google Scholar, and Textbook. Efforts to improve neurodevelopment using the concept of a gut-brain-axis microbiota are essentially efforts to create a good microbiota balance in the gut.  These efforts include maintaining and maintaining the balance of the healthy microbiota of pregnant women, giving birth pre-vaginal, providing exclusive breast milk, reducing the use of antibiotics that are not required, providing complementary foods breast milk rich in probiotics and prebiotics, providing stimulus, and reduce the use of chemicals.  The concept of gut-brain-axis microbiota is very applicable to maximize neurodevelopment in infants starting by paying particular attention to the prenatal and postnatal periods.